Knowledge, attitude, practice of rational use of medicines among junior residents in a tertiary care hospital - V., Hooli Tanuja; Srikanth, .; S. C., Somashekara; B., Suraj (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Irrational use of prescribing is on the rise due to many factors like false beliefs, following a prescribing pattern of senior doctors, inadequate knowledge, ignorance, promotional activities for the profit of professionals by pharmaceutical industry and lack of enforcement of regulations by regulatory authorities. Junior residents are exposed to variety of prescribing patterns in the first year and are the future physicians and specialists. There are very few studies among JRs, hence the present study was conducted to assess the knowledge, attitude and practice of junior residents about rational use of medicines. Methods: This was a cross-sectional, questionnaire based study conducted among JRs at a tertiary care hospital in South India in June 2015. The participants were explained about the study and consent was taken. Permission was obtained from institutional ethics committee. Identity of the residents was kept confidential. A self-developed, pre-validated, semi-structured questionnaire consisting of both open-ended and closed-ended items was used. Questionnaire was designed to obtain information about the knowledge, attitude and practice of RUM. The data was recorded and analyzed using Microsoft Excel (2013 version) and the results are explained in frequency and percentage. Results: The knowledge related to essential medicines list (EML), P drugs and schedule H drugs was limited. Participants had limited knowledge about the revision of EML list, number of fixed dose combinations (FDCs)in EML, STEP criteria for choosing a P drug and advantages of choosing a P drug Most of the JRs frequently prescribed drugs from EML. Trade name and newer drugs were prescribed around 50%. The prescription of FDCs from EML was very low (6%). Around 50% of JRs prescribe medicines with both generic and brand name. Conclusions: Majority of JRs were aware about various issues concerned with RUM but the knowledge related to EML, P drugs, schedule H drugs and number of FDCs in EML was limited. As junior residents are future prescribers, they need to be aware of all the aspects of RUM. Inadequate/improper knowledge in the above areas is a matter of concern and needs to be addressed.